From Surveillance to Prevention: Leveraging ICT Tools for Enhanced Crime Detection and Security Management - Agoi, Moses Adeolu; Sain, Zohaib Hassan; Agoi, Oluwanifemi Opeyemi (Nurul Jadid University, 2024)
Integrating revolutionary technologies in crime detection and prevention has transformed the landscape of modern security systems. This study aims to analyze the role and effectiveness of advanced Information and Communication Technology (ICT) tools, including facial recognition, thermal sensors, drones, GPS tracking systems, and real-time surveillance cameras, in enhancing crime prevention strategies. This research uses a descriptive survey approach. Data was collected through an online questionnaire distributed to 100 respondents using a non-probability sampling method. Data analysis uses a descriptive approach to describe the use of ICT in crime detection and prevention. The findings reveal that public awareness of ICT tools is increasing, with significant recognition of their potential to support connectivity, intelligence gathering, and proactive security measures. Advanced technologies were identified as essential in improving response times, enabling real-time monitoring, and enhancing the overall efficiency of crime prevention systems. Correlating with previous research, the study confirms that ICT tools provide innovative solutions for combating crime and fostering a sense of security within communities. These insights emphasize the need for continuous innovation and policy support to integrate cutting-edge ICT tools into law enforcement frameworks, ensuring adaptability to evolving security challenges.